Optimizing student success in school with the other three Rs : reasoning, resilience, and responsibility - Sternberg, Robert J.; Subotnik, Rena Faye (Research in educational productivity., 2006)
The Other Three R's model began as an American Psychological Association (APA) initiative, sponsored by Robert J. Sternberg, IBM Professor of Psychology and Education at Yale University and Past President of the APA. For both this initiative and this edited volume, Sternberg assembled a diverse team of experts who identified reasoning, resilience and responsibility as three learnable skills that, when taken together, have great potential for increasing academic success. The authors of this volume present in detail their evidence-based arguments for promoting TOTRs in schools as a way to optimize student success.